Moderasi Beragama dalam pendidikan Keagamaan Katolik Kelas VII - Br Ginting, Elisa; Br Ginting, Monika Handayani; Tindaon, Ronika (IN VERITATE LUX, 2023)
The Indonesian government's policy of religious moderation is the main subject of this study. The purpose of this study is to determine whether or not Catholic educators can implement and restore the religious moderation component included in Catholic education textbooks in classroom settings. There are four primary schools in the Tigabinanga district, three of them are state institutions and one private. As a result, religious moderation—that is, combining the techniques and information needed to create a multicultural knowledge base—has been implemented by Catholic educators. The teaching strategies and resources were adjusted to accommodate all pupils, demonstrating diversity, primitivism, stereotypes, and respect for gender, culture, and religion as well as the topics covered in Catholic Religious Education and ethics. Student reactions to intercultural knowledge-building and content integration procedures show this; 65% of students fall into the "Good" group, which highlights the need for diversity moderation. On the other hand, bias can be lessened by giving students clarity and explanations and by emphasizing honesty, accountability, respect for one another, and acceptance of painful past experiences. 69% of students gave the application of equality pedagogy and the decrease of bias in Catholic religious education a "Good" rating.